Eroding military influence in Brazil : politicians against soldiers - Hunter, Wendy (Chapel Hill : University of North Carolina Press, 1997)
"Major reconsideration of civil-military relations in post-authoritarian Brazil uses case studies of labor rights, federal budgeting, and control over Amazonia to argue that logic of competitive politics allowed civilian politicians to gradually erode military influence. Well researched and documented"--Handbook of Latin American Studies, v. 57.
Ch. 1. The Reduction of Military Influence in Postauthoritarian Brazil: Analytic Themes -- Ch. 2. Military Strength at the Inception of Civilian Rule -- Ch. 3. Military Prerogatives and Institutional Structures under the New Democracy -- Ch. 4. Labor Rights in Brazil's New Democracy: Politicians Rein in the Military -- Ch. 5. Budgetary Politics: Soldiers and Politicians Compete -- Ch. 6. Civil-Military Conflict over the Amazon.
Includes bibliographical references (pages 213-233) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Civil-military relations -- Brazil; Brazil -- Politics and government -- 1985-; Civil-military relations; Relations pouvoir civil-pouvoir militaire; Brésil -- Politique et gouvernement -- 1985-; Relations pouvoir civil-pouvoir militaire -- Brésil.; POLITICAL SCIENCE -- Political Process -- General; Civil-military relations; Politics and government; Brazil; Politik; Militär; Brasilien; Militairen; Democratie; Government - Central & South America; Government - Non-U.S.; Law, Politics & Government; Relations pouvoir civil-pouvoir militaire -- Brésil.; Brésil -- Politique et gouvernement -- 1985-2002.; Since 1985; Geschichte 1985-1994